Influences of parental socio-economic status on academic achievement: A case study of rural communities in Kailali, Nepal - Pant, Khagendra Raj (Contemporary Research: An Interdisciplinary Academic Journal, 2020)
The purpose of this study is to explore and analyze the relationship between the parental socio-economic status and academic achievement of students. The research question of the study was: How does the parental socio-economic status influence on academic achievement of students? This study focused on the interrelated dimensions of parental income, educational status, and its effect on children’s education. The study was conducted with a qualitative case study research design. Altogether 15 informants from parents, teachers, and students were selected by the purposive sampling method. In-depth interviews, focus group discussions, and observation techniques were followed during data collection. Data were analyzed using thematic narrative analysis. The study found that the majority of students of low socio-economic status have poor academic achievement. Parents of low economic background have been found less interested in the education of their children. Students from low socio-economic status more emphasized on employment rather than further study after secondary education. Such students were found to be pursuing unskilled jobs in labour market. This study recommended conducting free technical and vocational education. Schools and concerned authorities need to conduct parental awareness and education programs.